2017
DOI: 10.1007/s12289-017-1364-5
|View full text |Cite
|
Sign up to set email alerts
|

Large scale additive manufacturing of eco-composites

Abstract: The evolution of additive manufacturing processes is enabling the production of parts with improved dimensional accuracy, mechanical, physical and chemical properties [1]. New materials also contribute to this trend, and in this scope, eco-composites, materials with environmental and ecological advantages, which include natural polymers, have been acquiring increased relevance [2]. The purpose of this study is to develop composite material parts manufactured from recycled thermoplastics and natural fibres, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 9 publications
0
15
0
2
Order By: Relevance
“…Horta et al, (2017) so na robotsko roko pritrdili prirejen ekstrudor, ki z mešanico odpadnega HDPE in žagovine lahko tiska tudi večje izdelke. Podobni sistemi z različnimi tehnikami tiska in krmiljenja tiskalne glave npr.…”
Section: Slika 7 Ukrivljanje 3d-tiskanega Elementa Z Lesnimi Delci Sunclassified
“…Horta et al, (2017) so na robotsko roko pritrdili prirejen ekstrudor, ki z mešanico odpadnega HDPE in žagovine lahko tiska tudi večje izdelke. Podobni sistemi z različnimi tehnikami tiska in krmiljenja tiskalne glave npr.…”
Section: Slika 7 Ukrivljanje 3d-tiskanega Elementa Z Lesnimi Delci Sunclassified
“…When considering more remanufacturing cycles, though, Cruz Sanchez et al [37] showed that neat PLA is very prone to material degradation, as the tensile strength of 3D-printed samples deteriorated by approximately 40% after only five remanufacturing cycles. Although plenty of studies have recently investigated the processability of complex recycled regional postconsumer waste by FFF and have even recommended the use of so-called RecycleBots [38,39,40], such as blends of polyethylene [39,41,42,43,44,45], polypropylene (PP) [44,46,47,48,49,50], polyethylene terephthalate (PET) [49,50,51], acrylonitrile butadiene styrene (ABS) [49,52], poly(lactic acid) (PLA) [49,53], polystyrene (PS) [50], polyvinyl alcohol (PVA) [54], or polyamide (PA) [55], the effect of multiple AM and filament extrusion sequences on the processability of materials more complex than the standard FFF material PLA, which is known to be susceptible to thermal degradation [9], has not yet been studied. Moreover, neither the positive effect of thermal stabilizers on retaining mechanical strength [56] nor the degradation of a filler–matrix interface with increasing re-extrusion cycles [57] has been confirmed for advanced composites used in FFF.…”
Section: Introductionmentioning
confidence: 99%
“…Composites such as those described above are also under study for applications on AM processes. For instance, a wood-plastic composite consisting of high-density polyethylene and sawdust was used as feedstock for a large-scale fused deposition process by Horta [28]. It was possible to produce the material by extrusion and to manufacture large-scale parts, although process parameters require further tuning.…”
Section: Sustainabilty Issuesmentioning
confidence: 99%